The Influence of Customer Relationship Management (CRM) and Product Quality on Consumer Loyalty of Roti'O in Cimahi City - Murti Sari Dewi; Muji Rahayu (MASI Mandiri Edukasi, 2026)
This study aims to examine the impact of customer relationship management (CRM) and product quality on customer loyalty at Roti’o in Cimahi City. The research adopts a quantitative approach supported by descriptive and verification analysis. A total of 100 participants were selected using the Lemeshow formula and the purposive sampling technique. Data were collected using a closed-ended Likert-scale questionnaire and analyzed using multiple regression in SPSS version 25. The results indicate that CRM has a positive and significant effect on customer loyalty, whereas product quality does not show a significant influence. However, when tested simultaneously, both independent variables exhibit a significant effect on customer loyalty. These findings suggest that customer relationship management is the primary factor in building customer loyalty, while product quality remains a supporting element that enhances the overall consumption experience.